The Role of Prof. Syekh Ali Hasan Ahmad Ad-Dary on Hadith Studies in North Sumatera (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2018)
The aim of this research to describe the role and contributions of Prof. Syekh Ali Hasan Ahmad ad-Dary on hadith studies in North Sumatera. Applying the qualitative method, this research used primary data sources that were obtained from families (his son and his daughter), students as well as the books written by Prof. Syekh Ali Hasan Ahmad ad-Dary. The secondary data were obtained from various literature on the figure of Prof. Syekh Ali Hasan Ahmad ad-Dary related to the history of his life. The results of this study can be summaried in following points: Prof. Syekh Ali Hasan Ahmad ad-Dary was a figure who was very active on hadith studies in North Sumatera. It can be said the greatest role and contributions of Prof. Syekh Ali Hasan Ahmad ad-Dary on Hadith studies in North Sumatera was his attempt to write the books related to the Hadith and Hadith Sciences in North Sumatera. He is the pioneer of writing Hadith and Hadith studies books in this area. This can be seen from the year his book entitled Pokok-Pokok Musthalah Hadis:Untuk PGAN,SMIA dan Jang Sederadjat published by Pustaka Islamiyah, Medan in 1963. This book was the first musthalah hadith book published in North Sumatera. Then Prof. Syekh Ali Hasan Ahmad ad-Dary also published books of Hadith and Hadith Science through his publisher, Al-Mahfuzh Budi. Through his publisher, he published and distributed the books of Hadith and Hadith Studies. And the last of his role, Prof. Syekh Ali Hasan Ahmad ad-Dary was the first who holds a professor of Hadith in North Sumatera. This he received from President Soeharto dated 18 November 1976.